Die Einstandspflicht der Bundesrepublik Deutschland für die Deutsche Bundesbank und die Europäische Zentralbank - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
– In his paper, Helmut Siekmann comes to the conclusion that there is no warranty obligation of the Federal Republic of Germany for the Deutsche Bundesbank and the ECB.
urn:nbn:de:hebis:30:3-475949
Keywords: 330